Enhancing biomechanical machine learning with limited data: generating realistic synthetic posture data using generative artificial intelligence - Dindorf, Carlo; Dully, Jonas; Konradi, Jürgen; Wolf, Claudia; Becker, Stephan; Simon, Steven; Huthwelker, Janine; Werthmann, Frederike; Kniepert, Johanna; Drees, Philipp; Betz, Ulrich; Fröhlich, Michael (Frontiers in Bioengineering and Biotechnology, 2024)
Biomechanical Machine Learning (ML) models, particularly deep-learning models, demonstrate the best performance when trained using extensive datasets. However, biomechanical data are frequently limited due to diverse challenges. Effective methods for augmenting data in developing ML models, specifically in the human posture domain, are scarce. Therefore, this study explored the feasibility of leveraging generative artificial intelligence (AI) to produce realistic synthetic posture data by utilizing three-dimensional posture data collected from 338 subjects through surface topography. A Variational Autoencoder (VAE) architecture was employed to generate and evaluate synthetic posture data, examining its distinguishability from real data by domain experts, ML classifiers, and Statistical Parametric Mapping (SPM). Furthermore, this study assesses the benefits of incorporating augmented posture data into the learning process, as exemplified by a deep autoencoder (AE) for automated feature representation. Our findings highlight the challenge of differentiating synthetic data from real data for both experts and ML classifiers, underscoring the quality of synthetic data. This observation was also confirmed by SPM. By integrating synthetic data into AE training, the reconstruction error can be reduced compared to using only real data samples. Moreover, this study demonstrates the potential for reduced latent dimensions, while maintaining a reconstruction accuracy comparable to AEs trained exclusively on real data samples. This study emphasizes the prospects of harnessing generative AI to enhance ML tasks in the biomechanics domain.